Analiza umeščanja ljubljanske džamije - Kos, Drago (Teorija in praksa, 2013)
An analysis of the decades-long search for a site for an Islamic religious and cultural centre in Ljubljana highlights several key reasons which have caused the project to remain unfulfilled. The initial impulses and motives to erect a mosque were connected with piety values, and in the first phase specific ideas for the site of the mosque suggested the vicinity of Plečnik's Žale - Ljubljana's biggest cemetery. The political emancipation of the Islamic population in Yugoslavia played an important role in these developments. However, after two decades of discussions, a nationalist and exclusivist interpretation of Plečnik's architecture rendered any such site officially "completely unacceptable". Later, the search for a suitable site turned from representative areas to less visible, hidden and even degraded locations. A mosque or, rather, a house of prayer was only acceptable if its Islamic architecture was not too obvious and did not threaten "traditional spatial identities". What has been recommended is an abstract mimicry that would conceal the Islamic nature of the planned building from the lay public. In support of these ideas there has been an ambitious intention: to build the mosque in the emerging European Islamic style. This may even mean that it would no longer be necessary to "hide" the mosque, but to proudly present the new building as an example of the integrative and creative abilities of European/Slovenian architecture and (post)modern society in general.
Keywords: džamije; Ljubljana (Slovenia); Ljubljana (Slovenija); Mosques; Mošeje; Multiculturalism; Multikulturalizem; Prostorska sociologija; Spatial sociology; Toleranca; Tolerance